Sociocultural and psychological determinants in migrants for noncompliance with occlusion therapy for amblyopia - Tjiam, Angela M. (Springer-Verlag, 2011)
BACKGROUND: Compliance with occlusion therapy for amblyopia in children is low when their parents have a low level of education, speak Dutch poorly, or originate from another country. We determined how sociocultural and psychological determinants affect compliance. METHODS: Included were amblyopic children between the ages of 3 and 6, living in low socio-economic status (SES) areas. Compliance with occlusion therapy was measured electronically. Their parents completed an oral questionnaire, based on the “Social Position & Use of Social Services by Migrants and Natives” questionnaire that included demographics and questions on issues like education, employment, religion and social contacts. Parental fluency in Dutch was rated on a five-point scale. Regression analysis was used to describe the relationship between the level of compliance and sociocultural and psychological determinants. RESULTS: Data from 45 children and their parents were analyzed. Mean electronically measured compliance was 56 ± 44 percent. Children whose parents had close contact with their neighbors or who were highly dependent on their family demonstrated low levels of compliance. Children of parents who were members of a club and who had positive conceptualizations of Dutch society showed high levels of compliance. Poor compliance was also associated with low income, depression, and when patching interfered with the child’s outdoor activity. Religion was not associated with compliance. CONCLUSIONS: Poor compliance with occlusion therapy seems correlated with indicators of social cohesion. High social cohesion at micro level, i.e., family, neighbors and friends, and low social cohesion on macro level, i.e., Dutch society, are associated with noncompliance. However, such parents tend to speak Dutch poorly, so it is difficult to determine its actual cause. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00417-011-1637-5) contains supplementary material, which is available to authorized users.